Electric field induced macroscopic cellular phase of nanoparticles. Issue 10 (26th January 2022) - Rendos, Abigail; Cao, Wenhan; Chern, Margaret; Lauricella, Marco; Succi, Sauro; Werner, Jörg G.; Dennis, Allison M.; Brown, Keith A.
Abstract : Nanoparticles assemble into a macroscopic cellular phase upon the simultaneous application of an AC and DC voltage. First, the particles move through electrophoresis into a 2D film and then electrohydrodynamic flows cause spinodal decomposition. Abstract : A suspension of nanoparticles with very low volume fraction is found to assemble into a macroscopic cellular phase that is composed of particle-rich walls and particle-free voids under the collective influence of AC and DC voltages. Systematic study of this phase transition shows that it was the result of electrophoretic assembly into a two-dimensional configuration followed by spinodal decomposition into particle-rich walls and particle-poor cells mediated principally by electrohydrodynamic flow. This mechanistic understanding reveals two characteristics needed for a cellular phase to form, namely (1) a system that is considered two dimensional and (2) short-range attractive, long-range repulsive interparticle interactions. In addition to determining the mechanism underpinning the formation of the cellular phase, this work presents a method to reversibly assemble microscale continuous structures out of nanoscale particles in a manner that may enable the creation of materials that impact diverse fields including energy storage and filtration.